409PIntegrated genomic and transcriptomic analysis revealed mutagenic patterns of dedifferentiated liposarcoma and leiomyosarcoma in Chinese patients. (24th November 2019) - Zhou, Y; Lu, W; Zhang, Y; Tong, H; Liu, W; Zhuang, R; Guo, H
Abstract: Background: L-type sarcoma (liposarcoma + leiomyosarcoma) is the most common subtype of soft tissue sarcoma (STS). Leiomyosarcoma (LMS) and dedifferentiated LPS (DDLPS) are more aggressive with worse outcomes than well-differentiated sarcoma. Efforts have thus been made to decipher the difference of oncogenesis between DDLPS and LMS, and assist in the choice of treatment. Methods: WES was conducted on 32 STS (20 LMS and 12 DDLPS) and matched peripheral blood. Somatic SNVs and indels were identified by GATK tools. Recurrent somatic copy-number alterations (SCNA) were called using Control-FREEC and GISTIC2.0. We further conducted RNA-Seq on 8 DDLPS samples and 8 LMS samples, and use STAR-Fusion to reveal the distinct chromosome rearrangement patterns of LMS and DDLPS samples. Results: We identified top 20 highly variable genes between LMS and DDLPS. 55% LMS (n = 11) carry deletions or mutations of TP53. All DDLPS carry wildtype TP53, but chromosome 12q14–15 region which encodes MDM2, CDK4 and HMGA2 are highly amplified in all DDLPS samples, suggesting distinct mechanisms of TP53 pathway inactivation. Hippo pathway is reported to be involved in resistance to cytotoxic drugs and modulate tumour immunogenicity. In our study, 70% LMS (n = 14) and 58% DDLPS (n = 7) carry at least one Hippo pathway alterations, top variable genes in LMS include DCHS1, LLGL1, AJUBA et al. Among 8 LMS and 8 DDLPS who underwent RNA-Seq, we identified 4 fusion transcripts in 3 LMS and 36 fusion transcripts in 8 DDLPS (P = 0.007). Fusion transcripts involving chromosome 12 (Chr12) are only identified in DDLPS, including 10 interchromosomal and 12 intrachromosomal rearrangements. MDM2 and RAB3IP are the most common fusion partners. There was also significant correlation between MDM2/CDK4 co-amplification and Chr12 rearrangement (P < 0.001). All DDLPS with MDM2/CDK4 co-amplification showed elevated MDM2 and CDK4 co-expression. Conclusions: LMS and DDPLS carry distinct mutagenic patterns, ranging from SNVs to gross genomic instability. Chromosome rearrangement of DDLPS, particularly in Chr12, result in both gene amplification and fusion events, and these neoantigens produced by gene fusion may open up alternative avenues for immunotherapy. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.